2014
DOI: 10.5114/aoms.2014.47830
|View full text |Cite
|
Sign up to set email alerts
|

The association between the 844ins68 polymorphism in the CBS gene and breast cancer

Abstract: IntroductionThe cystathionine beta synthase (CBS) gene plays an important role in homocysteine metabolism because it catalyzes the first step of the transsulfuration pathway, during which homocysteine is converted to cystathionine. Polymorphisms of CBS have been associated with cancer.Material and methodsWe examined the role of the 844ins68 polymorphism by comparing the genotypes of 371 healthy Mexican women with the genotypes of 323 Mexican women with breast cancer (BC).ResultsThe observed genotype frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 57 publications
3
27
0
Order By: Relevance
“…In Mexico, BC represents one of the leading causes of death in working-age women (Chávarri-Guerra et al 2012;Miller et al, 2012;Gómez Flores et al, 2013;Ramírez-Patiño et al, 2013;Gallegos-Arreola et al, 2014). These facts are consistent with the observations made in the current study, where the average age of patients with BC was 54.17 (± 11.6) years.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In Mexico, BC represents one of the leading causes of death in working-age women (Chávarri-Guerra et al 2012;Miller et al, 2012;Gómez Flores et al, 2013;Ramírez-Patiño et al, 2013;Gallegos-Arreola et al, 2014). These facts are consistent with the observations made in the current study, where the average age of patients with BC was 54.17 (± 11.6) years.…”
Section: Discussionsupporting
confidence: 82%
“…All patients were also interviewed to determine their occupational exposure and as well as use of pharmacological therapies. The BC patient database and the DNA samples have been examined for other polymorphisms (Gómez Flores-Ramos et al, 2013;Ramírez-Patiño et al, 2013;Gallegos et al, 2014).…”
Section: Sample Collection and Patient Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Zhang et al observed an association between the CBS rs706209 polymorphism and clear cell renal cell carcinoma risk in the Chinese population35. Soon afterwards, Gallegos-Arreola and colleagues reported that the 844ins68 polymorphism in the CBS gene contributes significantly to breast cancer susceptibility in Mexican population36. Nevertheless, negative results have been observed with regard to different types of cancer373839.…”
Section: Discussionmentioning
confidence: 99%